KEANEKARAGAMAN JENIS TUMBUHAN OBAT DI HUTAN ADAT RIMBO TUJUH DANAU DESA BULUH CINA KABUPATEN KAMPAR PROVINSI RIAU - Stevi Istiqfar; Defri Yoza; Rudianda Sulaeman (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this research is to know about type of composition and diversity of medicinal plants in Customary Forest of Rimbo Tujuh Danau at Buluh Cina village. This research using methods purposive sampling. Data analysis using the Important Value Index (IVI) and Shannon Wiener diversity index (H’). The results showed that there were 38 types of 26 family composition type was found in Customary Forest of Rimbo Tujuh Danau. Vegetation type that have potentially as medicinal plants are 16 types of 13 family. The value of species diversity on tree level is 1,90, the poles is 1,00, the sapling is 1,00, the seedling and plants is 1,63 which the figures is indicated that the diversity of medicinal plants in Customary Forest of Rimbo Tujuh Danau have good worth with the value is 1≤H’<3. Keywords:Medicinal plants, Typeof composition, Species diversity,Customary Forest of Rimbo Tujuh Danau